# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = 40 \,{\mathrm e}^{2 x} x
\] |
✓ |
✓ |
|
\[
{}\left (x +6\right )^{{1}/{3}} y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x -1}{1+x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 = \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime }-\sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 = \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (\frac {x}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (\frac {x}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (\frac {x}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \sqrt {x +3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \sqrt {x +3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \sqrt {x +3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \sqrt {x +3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{\sqrt {x^{2}+5}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-9 x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sin \left (x^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left \{\begin {array}{cc} 0 & x <0 \\ 1 & 0\le x \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left \{\begin {array}{cc} 0 & x <1 \\ 1 & 1\le x \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left \{\begin {array}{cc} 0 & x <1 \\ 1 & 1\le x <2 \\ 0 & 2\le x \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 x y = 6 x
\] |
✓ |
✓ |
|
\[
{}\sin \left (x +y\right )-y y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime }-y^{3} = 8
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+x y^{2} = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y^{2} = x
\] |
✓ |
✓ |
|
\[
{}y^{3}-25 y+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right ) y^{\prime } = 3+y
\] |
✓ |
✓ |
|
\[
{}\left (y-2\right ) y^{\prime } = x -3
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y-y^{2} = -2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\left (8-x \right ) y-y^{2} = -8 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y^{2}-y^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x -y \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \left (x -y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = 8
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = 4 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y-3 x -2 y+6
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = {\mathrm e}^{x -3 y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}+9
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = y^{2}+9
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+y^{2}}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{2 x -3 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x -1+2 x y-y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x y^{2}+x
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 3 \sqrt {x y^{2}+9 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y-4 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-4 y = 2
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x y^{2}-9 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{y^{2}+x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 200 y-2 y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y-4 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y-3 x -2 y+6
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y^{2}-y^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {6 x^{2}+4}{3 y^{2}-4 y}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}-1\right ) y^{\prime } = 4 x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-y}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2+\sqrt {x}}{2+\sqrt {y}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 x^{2} y^{2} = -3 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 x^{2} y^{2} = 3 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 200 y-2 y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = -10
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x -1+2 x y-y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y^{2}-y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y^{2}-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}-1}{x y}
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}-1\right ) y^{\prime } = 4 x y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+3 x^{2} y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{2}+3 x^{2} y = \sin \left (x \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime }-x y^{2} = \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+\left (x y+3 y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x y+3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 y+8
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-{\mathrm e}^{2 x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = y^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\cos \left (x^{2}\right ) = 827 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 6
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 20 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 y+16 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+3 y-10 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {x}+3 y
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime }+y \sin \left (x \right ) = \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|